Report of a Working Group on Allium (Third meeting): held at the Institute of Horticultural Research, Wellesbourne, Warwick, UK, 5 and 8 September 1988 - International Board for Plant Genetic Resources; European Cooperative Programme for the Conservation and Exchange of Crop Genetic Resources (1988)
Report of the ECPGR Allium Working Group meeting, third meeting, 5-8 September 1988, Wellesbourne, Warwick, UK